microRNAs in action: biogenesis, function and regulation - Shang, Renfu; Lee, Seungjae; Senavirathne, Gayan; Lai, Eric C (Nature reviews. Genetics, 2023)
Ever since microRNAs (miRNAs) were first recognized as an extensive gene family >20 years ago, a broad community of researchers was drawn to investigate the universe of small regulatory RNAs. Although core features of miRNA biogenesis and function were revealed early on, recent years continue to uncover fundamental information on the structural and molecular dynamics of core miRNA machinery, how miRNA substrates and targets are selected from the transcriptome, new avenues for multilevel regulation of miRNA biogenesis and mechanisms for miRNA turnover. Many of these latest insights were enabled by recent technological advances, including massively parallel assays, cryogenic electron microscopy, single-molecule imaging and CRISPR-Cas9 screening. Here, we summarize the current understanding of miRNA biogenesis, function and regulation, and outline challenges to address in the future.